1992
DOI: 10.1021/bi00155a013
|View full text |Cite
|
Sign up to set email alerts
|

Binding of influenza virus hemagglutinin to analogs of its cell-surface receptor, sialic acid: analysis by proton nuclear magnetic resonance spectroscopy and x-ray crystallography

Abstract: The interaction between influenza virus hemagglutinin and its cell-surface receptor, 5-N-acetylneuraminic acid (sialic acid), was probed by the synthesis of 12 sialic acid analogs, including derivatives at the 2-carboxylate, 5-acetamido, 4-, 7-, and 9-hydroxyl, and glycosidic positions. The equilibrium dissociation constants of these analogs were determined by nuclear magnetic resonance spectroscopy. Ligand modifications that reduced or abolished binding included the replacement of the 2-carboxylate with a car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
244
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(261 citation statements)
references
References 65 publications
12
244
0
5
Order By: Relevance
“…S7), which agrees with the observations made during the AFM virus-cell pulling experiments. From NMR studies with purified ligands (20), the dissociation constant of X-31 HA to sialyllactose was reported to be 2.1 mM (2,6 linked) and 3.2 mM (2,3 linked). We suppose that these rather small differences observed using purified binding partners may not become obvious under conditions mimicking more closely the biological situation, as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7), which agrees with the observations made during the AFM virus-cell pulling experiments. From NMR studies with purified ligands (20), the dissociation constant of X-31 HA to sialyllactose was reported to be 2.1 mM (2,6 linked) and 3.2 mM (2,3 linked). We suppose that these rather small differences observed using purified binding partners may not become obvious under conditions mimicking more closely the biological situation, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The major spike protein hemagglutinin binds sialic acid residues of glycoproteins and glycolipids with dissociation constants in the millimolar range [Sauter NK, et al (1992) Biochemistry 31:9609-9621], indicating a multivalent binding mode. Here, we characterized the attachment of influenza virus to host cell receptors using three independent approaches.…”
mentioning
confidence: 99%
“…Characterization of A2-PC-QDs was performed by 5 direct MALDI-TOFMS (Nagahori et al, 2009;Ohyanagi et al, 2011) and the results showed the advent of an expected molecular ion signal at m/z 3155.7 corresponding to the heterodisulfide A2-S-S-PC instead of disappearance of the signal at m/z 908.7 due to ao-S-S-PC corresponding to free aminooxy-functional groups. As standards or simple model compounds in the competitive binding assay, 2-aminobenzamide (2AB) labeled A2 (2AB-A2, 1) (Dell et al, 2008), and two known sialosides, methyl 5-acetamido-3,5-dideoxy-D-glycero--D-galacto-2-nonulopyranosonic acid (2) (Sauter et al, 1992) and octyl 5-acetamido-3,5-dideoxy-D-glycero--D-galacto-2-nonulopyranosonic acid (3) (Crich and Li, 2007), were also used.…”
Section: Reagents and The Preparation Of A2-pc-qdsmentioning
confidence: 99%
“…3). To test the feasibility of this method for screening HA blockers as candidates for anti-influenza drugs, we employed preliminarily two known simple derivatives of sialic acid, methyl sialoside (2), which is already known to bind with the BroHA of X-31 strain (Sauter et al, 1992), and octyl sialoside (3). Each compound was added to a mixture of A2-PC-QDs and BroHA in the concentration range designated for the quantitative FP assay.…”
Section: Binding Assay By Competitive Fluorescence Polarizationmentioning
confidence: 99%
“…Because of the dramatic effect of the 25 mM soak on the native crystals, it was decided to proceed with cocrystallization at this concentration. This choice of concentration was also supported by the known dissociation constant of 2.3 sialyllactose from influenza hemagglutinin (Kd = 3.2 mM; Sauter et al, 1992). which has similar affinity and binding specificity to sialoadhesin (Crocker et al, 1991).…”
mentioning
confidence: 95%